Association between Prehospital National Early Warning Score (NEWS) And the older Patients’Mortality Rate - Hemwej, Thanaporn (Thai Journal of Emergency Medicine, 2023)
Introduction National Early Warning Score (NEWS) is one of the recognized tools for the early identification of clinical deterioration using seven basic physiological findings. The use of the new score is primarily for adults within hospital settings. However, studies evaluating the NEWS in prehospital settings for older patients are limited. Objectives To determine the association of NEWS and 30-day mortality among older patients in the prehospital settings. Method A retrospective cohort study enrolled older patients age ≥65 years who visited the emergency department (ED) by emergency medical service (EMS) from 1 November 2021 to 1 February 2023. The data were collected from electronic medical record and medical record at the scene. The association between NEWS and 30-day mortality was assessed. Results Five hundred and seven patients were enrolled in this study. The 30-day mortality was 19.7%. Area under receiving operating characteristic curve (AUROC) was 0.726. NEWS ≥8 predicted mortality with sensitivity 73% (95%CI, 64-81) and specificity 63.6% (95%CI, 58.7-68.1). Conclusion Pre-hospital NEWS was associated with 30-day mortality in older patients. Therefore, pre-hospital NEWS may be useful to recognize early signs of clinical deteriorate in older patients and may be applied in emergency medical service in order to provide prompt an appropriate treatment to these patients.